The Relationship between a Woman and Nature in Empowering Orang Rimba through Education Depicted in Butet Manurung's The Jungle School - Ervin Suryaningsih (TEKNOSASTIK, 2023)
This study investigates a woman's characteristics that reflect the ecofeminist perspective in empowering Orang Rimba through education depicted in The Jungle School. In analyzing the problem, this study applied descriptive-qualitative research using ecofeminism. The theory of character and ecofeminism describes a woman character's characteristics and relationship with nature in empowering the local people who still kept their local wisdom. The data is obtained through close reading focusing on the character's actions, responses, and reactions in educating Orang Rimba. It reveals that the main character is described as an intelligent, creative, and courageous woman who supports her in creating eco-friendly education to save nature from exploitation and preserve the indigenous people's local wisdom.Keywords: a woman character, ecofeminism, education